The Influence of Financial Distress, Audit Tenure, and Sustainability Disclosure on Modified Going Concern Audit Opinions: Evidence from Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange - Dody Suhermawan; Muhammad Ayin; Irawan Sugiono (Journal of Managerial Sciences and Studies, 2026)
This study aims to examine the effect of financial distress, audit tenure, and sustainability disclosure on the acceptance of modified going concern audit opinions in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study employed a quantitative research approach using secondary data obtained from annual reports, audited financial statements, and sustainability reports published during the 2022–2024 observation period. The population consisted of 95 companies within the food and beverage subsector, while the final sample comprised 67 companies selected through purposive sampling techniques based on predetermined criteria. Data analysis was conducted using descriptive statistical analysis and logistic regression analysis. The results indicate that financial distress has a significant effect on the acceptance of modified going concern audit opinions. Companies experiencing higher levels of financial distress are more likely to receive modified going concern audit opinions due to increased uncertainty regarding business continuity. Audit tenure also demonstrates a significant influence on the issuance of modified going concern audit opinions, indicating that the length of the auditor-client relationship affects auditors’ professional judgments concerning going concern assessments. In contrast, sustainability disclosure does not show a significant effect on the acceptance of modified going concern audit opinions, suggesting that auditors continue to prioritize quantitative financial indicators over non-financial sustainability information in evaluating going concern uncertainty. Simultaneously, financial distress, audit tenure, and sustainability disclosure collectively influence the acceptance of modified going concern audit opinions. This study contributes to the literature on auditing and corporate sustainability by providing empirical evidence regarding the determinants of modified going concern audit opinions within the Indonesian food and beverage manufacturing sector during the post-pandemic economic recovery period. The findings also reinforce agency theory by emphasizing the role of auditors as independent monitoring mechanisms in reducing information asymmetry and protecting stakeholders’ interests.